LOCAL SCOUR BELOW SUBMARINE PIPELINES EXPOSED TO IRREGULAR WAVE ATTACK - Kiziloz, Burak; Cevik, Esin Ozkan (YILDIZ TECHNICAL UNIV, 2013)
Submarine pipelines are widely used coastal structures, and scour around them can influence their stability. In this study, scour around rigid submarine pipelines in shoaling region under normal-incidence irregular wave attack on horizontal and (1/10) sloping beaches is studied. This paper presents experimental results concerning scour under irregular wave attack. Multiple regression analysis is used to develop models to predict the scour depth under pipelines under the influence of irregular wave attack. Any one of the models with different representative wave parameters could be used for the calculation of the scour depth below submarine pipelines exposed to irregular wave attack in practical engineering situations.
Keywords: Pipeline; scour depth; irregular wave; DEPTH; Engineering